Nature imagery's influence on ERN amplitude: an examination of Attention Restoration Theory using EEG - Collins, Sara A.; McDonnell, Amy S.; Scott, Emily E.; McNay, Glen D.; Shannon, Mary F.; Augustin, Lensky; Hoffmann, Janet Nicole; Johnson, Sharde; Strayer, David L.; LoTemplio, Sara B. (Frontiers in Human Neuroscience, 2025)
Empirical research on the mental health and cognitive benefits of nature immersion has expanded significantly in recent decades, building support for Attention Restoration Theory. However, the field still faces interpretive challenges due to inconsistent definitions of ‘nature' (whether nature imagery, real-world nature immersion, or other forms) and varied methodologies, which collectively limit our understanding of the underlying mechanisms that potentially drive these benefits. Addressing some of these limitations, the current study investigated whether exposure to virtual nature imagery influences attention restoration, as measured by the amplitude of the error-related negativity (ERN), similarly to real-world nature. In a repeated-measures randomized control design, 63 participants completed the Eriksen Flanker Task at three testing sessions. At Session 1, participants completed the task after viewing a neutral stimulus for 10 minutes. At Session 2, participants completed the task after viewing either nature or urban imagery for 10 minutes. At Session 3, participants completed the task after viewing the neutral stimulus again for 10 minutes. The ERN component generated from the Eriksen Flanker Task was quantified at each of the three testing sessions to assess changes in cognitive control and error monitoring associated with viewing different types of environmental imagery. Results showed no significant differences in ERN amplitude across sessions or between nature imagery and urban imagery at Session 2. Collectively, these results suggest that brief exposure to the 2-D nature imagery used within this study may not elicit the same attention-dependent responses as real-world nature exposure.